Automatic assessment of percussion rhythm imitation - Bachhas, Nikita (Nanyang Technological University, 2023)
Percussion instruments are an essential part of any music, in any genre. Percussionists often spend years learning to master a singular instrument and the training required to be a professional percussionist is rigorous. As such, the purpose of this project is to design and develop an application that allows for the automatic assessment of percussion imitation with the target users being serious beginners who wish to have percussion training. Users will be required to listen to a beat and then in their best attempt, try to recreate it. These two beats will be evaluated and compared by a linear programming assessment algorithm. This report provides the requirements analysis, the design and the planning, the implementation, the final results of the application and the results of a user study carried out.